Green Supply Chain Management: A Review based on Functionality (Journal of Informatics Education and Research, 2025)
The purpose of this paper is to review the relationships between environmental consciousness of the consumers and its effect on green purchasing, green operations and green marketing. It provides a classification based on functionalities in green supply chain management. Customers are today more and more environment-conscious and they want environment-friendly products. To this end, they influence purchasing, operations and marketing, thus resulting in green purchasing, green operations and green marketing. Reverse logistics is also an attempt to meet these needs. The paper reviews green purchasing, green operations and green marketing for the past twenty years and arrives at the conclusion that environmental consciousness has grown among consumers and they are willing to purchase environmentally-safe products.